Regional differences in precipitating factors of hospitalization for acute heart failure: insights from the REPORT‐HF registry. (17th February 2022) - Tromp, Jasper; Beusekamp, Joost C.; Ouwerkerk, Wouter; van der Meer, Peter; Cleland, John G.F.; Angermann, Christiane E.; Dahlstrom, Ulf; Ertl, Georg; Hassanein, Mahmoud; Perrone, Sergio V.; Ghadanfar, Mathieu; Schweizer, Anja; et al.
Abstract : Aims: Few prior studies have investigated differences in precipitants leading to hospitalizations for acute heart failure (AHF) in a cohort with global representation. Methods and results: We analysed the prevalence of precipitants and their association with outcomes in 18 553 patients hospitalized for AHF in REPORT‐HF (prospective international REgistry to assess medical Practice with lOngitudinal obseRvation for Treatment of Heart Failure) according to left ventricular ejection fraction subtype (reduced [HFrEF] and preserved ejection fraction [HFpEF]) and presentation (new‐onset vs. decompensated chronic heart failure [DCHF]). Patients were enrolled from 358 centres in 44 countries stratified according to Latin America, North America, Western Europe, Eastern Europe, Eastern Mediterranean and Africa, Southeast Asia, and Western Pacific. Precipitants were pre‐with mutually exclusive categories and selected according to the local investigator's discretion. Outcomes included in‐hospital and 1‐year mortality. The median age was 67 (interquartile range 57–77) years, and 39% were women. Acute coronary syndrome (ACS) was the most common precipitant in patients with new‐onset heart failure in all regions except for North America and Western Europe, where uncontrolled hypertension and arrhythmia, respectively, were the most common precipitants, independent of confounders. In patients with DCHF, non‐adherence to diet/medication was the most common precipitant regardless of region. Uncontrolled hypertension was a more likely precipitant in HFpEF, non‐adherence to diet/medication, and ACS were more likely precipitants in HFrEF. Patients admitted due to worsening renal function had the worst in‐hospital (5%) and 1‐year post‐discharge (30%) mortality rates, regardless of region, heart failure subtype and admission type ( p interaction  >0.05 for all). Conclusion: Data on global differences in precipitants for AHF highlight potential regional differences in targets for preventing hospitalization for AHF and identifying those at highest risk for early mortality. Abstract : Overview of the methods and results of this study.